Alternatives to rapid weight loss in US wrestling - Lambert, C.; Jones, B. (International Journal of Sports Medicine, 2010)
Amateur wrestling at the high school and collegiate level in the United States often involves exercise and thermal dehydration as well as food and fluid restriction to "make weight". Available evidence suggests this is the opposite of what is optimal for high-intensity exercise performance. A high-intensity taper will substantially improve performance when conducted after a period of high-volume high intensity training. Additionally, dehydration of appr. 3-4% of body weight will most definitely impair muscular endurance during high-intensity exercise although it likely will not impair maximal muscular strength or power. Even more gradual weight loss practices over a few days, which result in a reduction of body weight by appr. 3.3 to 6% will result in impaired performance as assessed by wrestling specific tests. It would seem of paramount importance for wrestlers to maintain a high-carbohydrate diet of appr. 8-10 g carbohydrate/kg body weight/day to maintain training intensity and optimize performance during individual matches and tournaments. Thus, the evidence would suggest that, prior to competition, collegiate wrestlers should be: 1) tapered, 2) in the euhydrated state, and 3) have ingested a high carbohydrate diet, rather than undergo rapid weight loss prior to competition.